Integrated metabolomic and transcriptomic analysis of the mechanism underlying leaf variegation in Miscanthus sinensis ‘Zebrinus’ - Han, Yu-Lan; Cheng, Yi-Shan; Li, Yi-Xin; Luo, Deng-Jin; Cai, Ming; Mu, Lan (Frontiers in Plant Science, 2026)
IntroductionMiscanthus sinensis ‘Zebrinus’ is a landscape plant with high ornamental value, whose core ornamental feature is determined by the irregularly distributed yellow variegation on its leaves, supporting its extensive application in landscape design and configuration. M. sinensis ‘Zebrinus’, as a typical variegated-leaf gramineous plant, possesses a key phenotypic trait of leaf variegation that distinguishes it from ordinary Miscanthus species. However, up to the present moment, we know little about the molecular regulatory mechanism underlying this unique variegation, with relevant research carried out in the exploratory stage.MethodsThis study was performed with the use of two leaf phenotypes [Yellow area of variegated leaves (YS) and Green area of variegated leaves (GS)] of M. sinensis ‘Zebrinus’. Differential metabolites between GS and YS leaf samples was conducted using the metabolomic analysis, with a focus on identifying key metabolites associated with leaf variegation. Furthermore, gene expression profiles of GS and YS leaves were acquired through transcriptome sequencing. With the screening of differentially expressed genes (DEGs), this study also carried out functional annotation and pathway enrichment analysis. Moreover, the expression levels of candidate genes in GS and YS leaves were measured via quantitative real-time polymerase chain reaction (qRT-PCR). In addition, a “gene-metabolite” regulatory network was constructed by integrating the metabolomic and transcriptomic data to screen out the key metabolites and core genes responsible for regulating leaf variegation in M. sinensis ‘Zebrinus’.ResultsMetabolomic analysis identified 4,036 common metabolites in GS and YS samples, with major enrichment in the flavonoid biosynthesis pathway. Secondary classification of this pathway indicated that flavonoids had the highest content. Further comparison of the expression levels of key metabolites revealed that the accumulation patterns of neohesperidin, taxifolin, naringenin, and xanthohumol in YS were all higher than those in GS, with naringenin showing the most significant difference, suggesting that it might be the core metabolite regulating leaf spot formation. According to subsequent transcriptome sequencing, 5,252 DEGs were screened out from the YS and GS samples, which were mainly enriched in flavonoid biosynthesis phenylpropanoid biosynthesis and other pathways. qRT-PCR presented the highest expression level in chalcone synthase (CHS). Integration of metabolome and transcriptome demonstrated significant enrichment of differential metabolites and DEGs in the flavonoid biosynthesis pathway. Additionally, correlation network graph analysis suggested the highest correlation of naringenin with CHS.DiscussionThis study identifies the core intrinsic regulatory mechanism underlying leaf variegation in M. sinensis ‘Zebrinus’ through integrated metabolomic and transcriptomic analysis. CHS has a strong correlation with naringenin, suggesting that the transcriptional regulation of the CHS gene may directly affect the biosynthesis of naringenin. The synergistic effect of the two may be one of the key molecular mechanisms underlying the formation of yellow leaf variegation.